Knowledge, attitude and practices about antimicrobial resistance and appropriate use of antimicrobial agents among the MBBS students of a medical college hospital in Eastern India - Ghosh, Abhishek; Das, Snehasish; Dasgupta, Raju (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Antimicrobial agents are one of the most commonly used as well as misused drugs. Rational antibiotic use is thought to be the best way to control resistance. Awareness and practice about antimicrobial use and resistance among medical students of different years so that appropriate measures can be taken to educate them properly to prevent misuse of antimicrobial as far as possible. Methods: It was a cross sectional questionnaire-based study undertaken in a teaching hospital in Eastern India among 328 medical students in 4 different batches. their responses remained confidential. total correct and incorrect responses from each of the 4 batches of MBBS students. overall trend and batch wise difference in the responses were analyzed. Results: Most of them had idea about problem of antimicrobial resistance and most of the students answered majority of the questions correctly. While assessing difference in responses in different batches, result showed that there was very significant improvement in the response of 6th semester students than the response of 4th semester students, may be due to acquiring knowledge of antimicrobials from their pharmacology classes in that period. Conclusions: Overall knowledge of antimicrobial resistance and proper use of antimicrobials appears good among different batches of MBBS student of this institution, though some areas need to be improved. Knowledge improvement is most evident from 4th semester to 6th semester students. Pharmacology training appears to make students more aware of this problem. Regular education is important to make them more aware.